The native brotherhoods modern intertribal organizations on the Northwest coast - Drucker, Philip 1911-1982 (United States Gov. Print. Off., 1958)
A study of the Alaska Native Brotherhood and the Native Brotherhood of British Columbia. Appendices include constitutions of the two societies.
Keywords: Alaska Native Brotherhood; Native Brotherhood of British Columbia; Aculturación; Indios de América del Norte - Costa Noroeste; Indianer; Acculturation; Indians of North America -- Northwest Coast of North America